Zonguldak ve Devrek'in iklim özellikleri - Hangül, Ezgi Gamze (My University, 2020)
ÖZETİklim, doğal ortam, insan yaşamı ve faaliyetleri üzerinde oldukça etkili birunsurdur. Bu nedenle bir sahanın ikliminin bilinmesi önem taşımaktadır. Bu çalışmadaBatı Karadeniz Bölümü’nde bulunun Zonguldak ve Devrek’in iklim özellikleriincelenmiş ve karşılaştırılmıştır. Zonguldak ve Devrek’in 1965-2018 yılları arasındabulunan iklim verileri Meteoroloji Genel Müdürlüğü’nden temin edilmiş ve analizleriyapılmıştır. Elde edilen sonuçlar tablo ve grafikler haline dönüştürülerek desteklenmiştir.Ayrıca Köppen, De Martonne, Thornthwaite ve Erinç metotları kullanılarak Zonguldakve Devrek’in iklim sınıflandırmalarındaki yeri ve özellikleri belirlenmiştir.Zonguldak ve Devrek iklim bakımından benzer özellikler gösterirler. Ancak,iklim elemanları değerlendirildiğinde bazı farklılıklar bulunmaktadır. İki istasyonsıcaklık şartları bakımından birtakım farklılıklar göstermekle birlikte, yağış şartlarınagöre belirgin farkları vardır. Zonguldak’ın yıllık ortalama sıcaklığı 13,8°C, Devrek’in14,2°C’dir. Yıllık ortalama yağış Zonguldak’ta 1210,7 mm iken Devrek’te 769,1 mm’dir.Rubinstein formülüne göre Zonguldak’ın hâkim rüzgâr yönü S 37° E olup %42,4frekanslıdır. Devrek’te ise yıllık hâkim rüzgâr yönü %37,4 frekans ile N 18° Esektörlüdür, ikinci dereceden hâkim rüzgâr yönü S 31° W’dir ve %41’lik frekansasahiptir. İklim sınıflandırmalarına göre benzerlikler olduğu kadar farklılıklarda bulunur.Köppen tasnifine göre; Zonguldak ve Devrek orta iklimler kuşağında, nemli ılımaniklimlerden kışı ılık, yazı çok sıcak, her mevsim yağışlı iklim içerisine girmektedir. DeMartonne tasnifine göre; Zonguldak ve Devrek Oseanik orta kuşak iklimine girmektedir.Erinç yağış etkinlik indisine göre Zonguldak çok nemli iklim, bitki örtüsü çok nemcilorman. Devrek ise yarı nemli iklim, bitki örtüsü park görünümlü kurak orman sınıfa girer.Yapılan çalışmada tüm veriler sonucunda, Zonguldak’ta Karadeniz iklimi hükümsürerken Devrek’te, Karadeniz iklimine benzer özellikler görülmekle birlikte, karasaletkilerin de kendini gösterdiği tespit edilmiştir.

ABSTRACTClimate; natural environment is very influential element of human life andactivities. Therefore, it is important to know of an area's climate. In this study, the climaticcharacteristics of Zonguldak and Devrek in the Western Black Sea Region were examinedand compared. Between the years 1965-2018 The climate data of Zonguldak and Devrekwere obtained from the General Directorate of Meteorology and analyzed. The obtainedresults are supported by transforming them into tables and graphics. Also; the place andcharacteristics of Zonguldak and Devrek in climate classifications were determined byusing Köppen, De Martonne, Thornthwaite and Erinç methods.Zonguldak and Devrek show similar characteristics in terms of climate.However, there are some differences when the climatic elements are evaluated. Althoughthe two meteorological observation stations show similar characteristics in terms oftemperature conditions, there are important differences according to precipitationconditions. The mean yearly temperature of Zonguldak is 13,8° C, and the temperatureof Devrek is 14,2° C. While the mean annual precipitation is 1210.7 mm in Zonguldak, itis 769.1 mm in Devrek. According to Rubinstein's formula; the prevailing wind directionof Zonguldak is S 37° E with a frequency of %42.4. In Devrek; the annual prevailingwind direction is N 18° E sector with a frequency of %37.4, the second-degree prevailingwind direction is is S 31° W and has a frequency of %41. In addition, according to climateclassification, there are also differences as well as similarities. According to the Köppenclassification; Zonguldak and Devrek are in the mild temperate zone, from humid/ moisttemperate climates to a climate that is mild winters, very hot in summer and rainy in allseasons. According to De Martonne classification; Zonguldak and Devrek fall intooceanic climate zone. According to Erinç’s Precipitation Efficiency Index; Zonguldakvery humid climate, vegetation is very humid forest; Devrek is classified as a semi-humidclimate and an arid forest with a park-like vegetation. As a result of all the data in thisstudy, it has been determined that while the Black Sea climate prevails in Zonguldak,characteristics similar to the Black Sea climate are observed in Devrek, but terrestrialeffects also manifest themselves.
Keywords: basınç; buharlaşma Geography; climate; Coğrafya; evaporation; Fiziksel coğrafya; Geography; iklim; moisture; nem; Physical geography; precipitation; pressure; rüzgâr; sıcaklık; temperature; wind; yağış